The Impact of Employee Performance on Workplace Conflict and Organizational Culture among Indonesian Workers - Nina Herlina; Dwi Putrigarini; Lia Yulia; Guo Xinghao (PT. BATARI EDU CALYA, 2024)
This study aims to examine the influence of work conflict and organizational culture on employee performance at PT. PG Rajawali II Cirebon. The research employs an associative design with a quantitative approach. The population consisted of all employees of PT. PG Rajawali II Cirebon, with a sample of 89 respondents selected as research participants. Data were collected through structured questionnaires. Classical assumption tests, including normality and multicollinearity tests, were conducted prior to hypothesis testing. Multiple linear regression analysis was utilized to examine the relationships between variables, while the coefficient of determination (R²) was applied to measure the proportion of variance in employee performance explained by the independent variables. Hypothesis testing was performed using t-tests (partial effects) and F-tests (simultaneous effects). The results indicate that work conflict has a positive and statistically significant effect on employee performance. Organizational culture also demonstrates a positive and significant influence on employee performance. Simultaneously, work conflict and organizational culture significantly affect employee performance. These findings imply that effective conflict management and the strengthening of organizational culture are essential strategies for enhancing employee performance at PT. PG Rajawali II Cirebon. Future research is recommended to explore additional variables that may contribute to employee performance in a broader industrial context and to conduct more in-depth analyses of mechanisms for optimizing conflict management and organizational culture development.